2017
DOI: 10.21276/ap.2017.6.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the phytochemical traits and their correlation with quantitative characters of MonardacitriodoraCerv. ex Lag

Abstract: Evaluation of phytochemical traits and their correlation studies were conducted with special reference to the quantitative characters of Monarda citriodora Cerv. ex Lag. A field experiment was carried out during two successive cropping seasons of 2014 and 2015 at Field Research Station, Chatha, CSIR -Indian Institute of Integrative Medicine, Jammu to study the effect of four irrigation frequencies (irrigation at 30 (F 1 ), 20 (F 2 ), 15 (F 3 ) and 12 (F 4 ) days interval with four nitrogen levels, viz., N 0 (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…Several authors reported that NPK fertilizer significantly enhanced the production of essential oils and active ingredients of some medicinal and aromatic plants, such as Monarda citriodora, [8,17]. Ocimum basilicum L. [18,19] and Satureja hortensis, [20].…”
Section: Introductionmentioning
confidence: 99%
“…Several authors reported that NPK fertilizer significantly enhanced the production of essential oils and active ingredients of some medicinal and aromatic plants, such as Monarda citriodora, [8,17]. Ocimum basilicum L. [18,19] and Satureja hortensis, [20].…”
Section: Introductionmentioning
confidence: 99%